P046 HISTOLOGIC MEASURES OF MUCOSAL HEALING CORRELATE WITH ENDOSCOPIC MEASURES OF DISEASE ACTIVITY AT BASELINE AND FOLLOWING INDUCTION THERAPY WITH THE JANUS KINASE 1 INHIBITOR FILGOTINIB IN ACTIVE CROHN'S DISEASE: RESULTS FROM FITZROY STUDY. (18th January 2018) - Reinisch, Walter; D'Haens, Geert; Hertogh, Gert De; Van der Aa, Annegret; Etchevers K, Kim; Tasset, Chantal; Yun, Chohee; Serone, Adrian; Feagan, Brian; Sandborn, William J; Vermeire, Séverine
Abstract: Background: Filgotinib (fil), a selective JAK1 inhibitor, has shown efficacy in a randomized double-blind, placebo (pbo)-controlled phase 2 study in Crohn's disease (CD) (FITZROY [1]), which included centrally read endoscopy and histopathology assessments after 10-week induction treatment. Methods: Patients (N=174) were randomized 3:1 to 200-mg fil (n=130) or pbo QD (n=44) (1). Biopsies were collected at baseline (BL) and Week 10 from the most affected areas of the predefined bowel segments (ileum, ascending, transverse, descending, sigmoid colon and rectum). This post hoc analysis explores the correlation between BL and post-induction histologic and endoscopic disease activity by comparing total scores and activity subscores (a) for the Ileal and Colonic Global Histology Activity Score (IGHAS/CGHAS) vs total Ileal and Colonic Simplified Endoscopic Score for CD (ISES-CD/CSES-CD) or ulcer subscores (u; sum of size and % affected surface) in patients with available readings in all segments. Results: BL values were similar across treatments, although CGHAS and CSES-CD were numerically higher in the pbo group (Table 1). After 10 weeks of fil treatment, CGHAS and (a)CGHAS significantly improved, together with macroscopic changes in (u)CSES-CD. Changes in ileal segment histology scores were numerically greater with fil vs pbo. Histology total and subscores were significantly associated with total and endoscopic ulcer subscores at both time points, and more pronounced in the colonic vs the ileal segments. Conclusions: Fil-induced endoscopic score improvements follow histologic score reductions, both in colonic and ileal segments. However, as in prior studies (2, 3), colonic mucosa was more prone to improve than ileal mucosa. There were no spontaneous reductions of histologic activity with pbo. REFERENCES: 1. Vermeire S, et al. Lancet. 2017; 389(10066):266–75. 2. Geboes K, et al. Curr Med Res Opin. 2005;21(11):1741–54. 3. Reinisch W, et al. J Crohns Colitis. 2017;11(4):425–34.